KANDUNGAN SENYAWA KIMIA, UJI TOKSISITAS (Brine Shrimp Lethality Test) DAN ANTIOKSIDAN (1,1-diphenyl-2-pikrilhydrazyl) DARI EKSTRAK DAUN SAGA (Abrus precatorius L.) - Juniarti, Juniarti; Osmeli, Delvi; Yuhernita, Yuhernita (Makara Journal of Science, 2009)
Chemical Compound Gynecology, ToxinTest (Brine Shrimp Lethality Test) and Antioxidants (1,1-Diphenyl-2- Pikrilhydrazyl) from Saga Leaf Extract (Abrus Precatorius L.). Cytotoxicity effects and antioxidant activities of saga (Abrus precatorius L.) extract were studied by using Brine Shrimp Lethality Test and 1,1-diphenyl-2-pikrilhydrazyl assays. Saga was extracted with different solvents i.e n-hexane, ethyl acetate and methanol. Result showed that the methanolic extract of saga had been potential to be cytotoxic againts Brine Shrimp with LC50 value of 606.736 ppm. However, all the extract of saga did not have antioxidant activities.